Perbedaan Jenis Frasa Nominal dan Kata Majemuk Nomina - Baiq Yulia Kurnia Wahidah (Peneliti.net, 2021)
Differences in the form a noun phrase and the noun form of the word mejemuk often found in its use both in a scientific paper or literature. The problem in this research is the difference in the form of a noun phrase and form compound nouns. Therefore the aim of this study was to describe the differences between the shape and form of a noun phrase noun mejemuk said. The method in this research use descriptive qualitative, ie to describe the form of phrases and compound words. Results from this study is a description of differences phrases and compound words.